Gambaran Penerapan Protokol Kesehatan 5 M Pada Mahasiswa Di Masa Pandemi Covid 19 - Susilowati, Tri; Nurromah, Anjar (Profesi (Profesional Islam) : Media Publikasi Penelitian, 2022)
Introduction; COVID-19 disease caused by the SARS-CoV 2 virus has made the world restless. Since February 2020, the increase in cases that occur continues to increase in Indonesia. More than 800,000 people in Indonesia have been infected with the coronavirus. The number of dead is above 25,000. The Indonesian government campaigns for the 3M movement to keep a distance, wear masks, wash hands in an effort to break the chain of spread of the corona virus. Now prevention is being increased to the implementation of 5M. Purpose; Knowing the description of the implementation of the 5 M health protocol to students of 'Aisyiyah University Surakarta during the Covid 19 pandemic. Methods; This research plan is descriptive research. The population of this study is all students of 'Aisyiyah University Surakarta as many as 1,304 students. A sample of 480 students. Sampling techniques use purposive sampling. The study variables were wearing masks, washing hands, physical distancing, staying away from crowds and limiting mobilization and interaction. The measuring instrument used in the study was a questionnaire with the answer choice being Always, Often, Sometimes, Rarely and Never. Data collection is done using google form and utilizing social media in the form of Whatsapp. The data will be presented in the form of tables and frequency distributions. Results; Most students always wear masks, namely 365 students (76%), always wash their hands, namely 280 students (54.2%), always do physical distancing, namely 170 students (35.4%), always stay away from the crowd of 185 students (38.5%) and often limit mobility and interaction, namely 192 students (40%). Conclusions; Most of the students have implemented the 5M Covid 19 health protocol.